HIV Wasting Syndrome in a Nigerian Failing Antiretroviral Therapy: A Case Report and Review of the Literature - Dimie Ogoina; Reginald O. Obiako; Haruna M. Muktar (Case Reports in Medicine)
The HIV wasting syndrome represented the face of HIV/AIDS before the advent of highly active antiretroviral therapy (HAART). Although the incidence of wasting has declined since the introduction of HAART, weight loss remains common in patients receiving HAART, especially in the setting of a failing HAART regimen. As we are not aware of any previous reports from Nigeria, we report a case of the classical wasting syndrome in a Nigerian female who had both virological and immunological HAART failure due to poor adherence. The influence of a failing HAART regimen, socioeconomic status, and other clinical variables in the wasting syndrome are discussed.